1993
DOI: 10.1177/105381519301700403
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Three Developmental Screening Tests

Abstract: Developmental screening tests are widely used for early identification but few are studied for their accuracy—the percentage of children with and without problems correctly detected. The absence of such data makes it difficult for professionals to choose measures wisely and to avoid those that under-detect or over-refer. In this article, the accuracy of three developmental screening tests was assessed. Measures included the Academic Scale of the Developmental Profile-II (DP-II), the Denver II, and the Battelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 16 publications
2
46
0
11
Order By: Relevance
“…Because of the reduced sensibility of the Denver I test for language development, a more complete test was developed, Denver II [16]. The Denver II test has improved sensibility for the detection of deficits in the area of language (>85%) [17]. We started our study in 1995, using the Denver I test, and from 1999 on we also began to use Denver II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the reduced sensibility of the Denver I test for language development, a more complete test was developed, Denver II [16]. The Denver II test has improved sensibility for the detection of deficits in the area of language (>85%) [17]. We started our study in 1995, using the Denver I test, and from 1999 on we also began to use Denver II.…”
Section: Discussionmentioning
confidence: 99%
“…The Denver II test increases coverage of language, allowing for greater fidelity/credibility in this area [16,17]. This test began being applied in the outpatient clinic of the neuropediatric unit of HC-UFPR at the end of 1999.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also enable healthcare providers to isolate specific problem areas, enabling interventions to be individually tailored to children. Although DDST-II is reported to have excellent sensitivity (low false negative rate) (83%), its low specificity (high false positive rate), has been questioned (Glascoe et al 1992;Glascoe 2002). On the other hand, other research has indicated that the high false positive rate can be reduced by means of clinical judgement and repeat screening and that it is a useful tool to identify children who are developmentally delayed, who would otherwise be missed (Lim et al 1996).…”
Section: Denver Developmental Screening Testmentioning
confidence: 99%
“…The BDT correctly classified 94% of the participants, an excellent hit rate. It also had an excellent sensitivity rate, correctly classifying 96.4% of the dyslexic group, well above the minimum recommended, 80% (Glascoe & Byrne, 1993). This high sensitivity rate ensures that the number of false negatives is kept to a minimum and that most adults who are at risk of dyslexia will be correctly identified.…”
Section: Validitymentioning
confidence: 82%